The Impact of Religious Tourism on Local Economic Growth: A Qualitative Study at Buddha Ko Mawoli Devdaha - Dhakal, Bhim Lal; Bhattarai, Yadab (Devkota Journal of Interdisciplinary Studies, 2026)
This research examines how religious tourism influences local economic growth, with a particular focus on Buddha ko Mawoli in Devdaha, Rupandehi, Nepal - a site deeply tied to the early life of Lord Buddha and rich in cultural and spiritual significance. Using a qualitative research methodology, the study delves into the ways religious tourism affects income levels, job creation, and infrastructure development within the community. Data was gathered through semi-structured interviews conducted with local residents, business owners, tourism professionals, and government officials, along with on-site observations. The results show that religious tourism has spurred economic progress, especially in sectors such as hospitality, traditional crafts, and transportation. Nonetheless, the research also points out key challenges, including subpar infrastructure, insufficient marketing, and the absence of long-term planning strategies. The study highlights the promise religious tourism holds for inclusive local development, while stressing the importance of well-thought-out initiatives and supportive policies to ensure sustained benefits. It adds valuable insights to ongoing conversations about sustainable tourism and regional advancement in culturally meaningful locations